2003
DOI: 10.1021/ac0263667
|View full text |Cite
|
Sign up to set email alerts
|

A Method for the Detection of Hydrocarbon Pollution in Soils by Headspace Mass Spectrometry and Pattern Recognition Techniques

Abstract: In the present work, we report a methodology for the rapid detection of soil pollution by hydrocarbons that is based on direct coupling of a headspace sampler with a mass spectrometer. With no prior treatment, the samples are subjected to the headspace generation process and the volatiles generated are introduced directly into the mass spectrometer, thereby obtaining a fingerprint of the sample analyzed. The mass spectrum corresponding to the mass/charge ratios (m/z) ranging between 49 and 160 atomic mass unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Additionally, a series of separative analyses by GC/MS was performed for confirmatory purposes to show the analytical potential of the nonseparative method. The method based on HS-MS has been previously used for the fast analysis of volatiles in different matrixes including water, 30,31 soil, 32 pharmaceuticals, 25 and food. 33 In this work, five biomarkers (methyl tert-butyl ether (MTBE), dimethyl disulfide, styrene, limonene, and 2-ethyl-1-hexanol) of both diseases and exposure to environmental pollutants were selected to check the possibilities of the proposed methodology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a series of separative analyses by GC/MS was performed for confirmatory purposes to show the analytical potential of the nonseparative method. The method based on HS-MS has been previously used for the fast analysis of volatiles in different matrixes including water, 30,31 soil, 32 pharmaceuticals, 25 and food. 33 In this work, five biomarkers (methyl tert-butyl ether (MTBE), dimethyl disulfide, styrene, limonene, and 2-ethyl-1-hexanol) of both diseases and exposure to environmental pollutants were selected to check the possibilities of the proposed methodology.…”
mentioning
confidence: 99%
“…Additionally, a series of separative analyses by GC/MS was performed for confirmatory purposes to show the analytical potential of the nonseparative method. The method based on HS-MS has been previously used for the fast analysis of volatiles in different matrixes including water, , soil, pharmaceuticals, and food …”
mentioning
confidence: 99%
“…Generally, data can be obtained by using the mass spectrum that represents the sum of intensities of all the ions detected during the data acquisition time . To date, a growing number of applications for this methodology have been reported that are related to quality control in foods such as olive oils or wines and hydrocarbon contamination in soils and waters. Classification or regression approaches were used for screening or quantification purposes according to the analytical problem addressed. Similarly, when using MIMS, the positive identification of individual analytes in the complex matrix that contains compounds with overlapping molecular ions (e.g., benzene, toluene, ethylbenzene, and p -xylene, BTEX) 4 requires, as in HS-MS, chemometric approaches since both methodologies use the same data acquisition in the MS.…”
mentioning
confidence: 99%
“…As an alternative to gas sensor electronic noses, a methodology based on the direct coupling of a headspace sampler with a mass spectrometer (HS-MS) has been proposed. …”
mentioning
confidence: 99%
“…Internal normalization involves expressing each mass intensity as a percentage of the total sum of intensities. This type of data treatment corrects the irreproducibility of the headspace sampler and sensitivity changes, provided they are constant along the mass axis. , No additional sample manipulation is needed, but the quantitative information is lost. It is appropriate for many characterization problems in which the “shape” of the profile signaland not the intensitycontains the relevant information.…”
mentioning
confidence: 99%